Effects of extended postmortem aging and intramuscular location on protein degradation, muscle fiber morphometrics, and tenderness of beef longissimus lumborum and semitendinosus steaks. (13th September 2021) - Matney, MaryAnn J; Gravely, Morgan E; O'Quinn, Travis G; Drouillard, James S; Phelps-Ronningen, Kelsey J; Houser, Terry A; Hobson, Allison W; Alcocer, Hanna M; Gonzalez, John M
Abstract: The objective of this study was to determine effects of extended aging and intramuscular location on Warner-Bratzler shear force (WBSF ), muscle fiber cross-sectional area (CSA ), and protein degradation of semitendinosus (ST ) and longissimus lumborum (LL ) steaks. Left ST and LL were removed from 40 carcasses at 6 d postmortem. The ST was fabricated into five locations (LOC ), with LOC 1 being most proximal and LOC 5 being most distal. The posterior LL was fabricated into 3 LOC, with LOC 1 being most anterior. Vacuum sealed ST steaks were aged 7, 14, 28, 56, or 112 d postmortem, while LL steaks were aged 7, 28, or 112 d postmortem at 2 ± 1 °C. A steak from each LOC was assigned to WBSF or laboratory analyses. There were no Day of Aging (DOA ) × LOC interactions for all dependent variables ( P > 0.06). There were DOA effects for ST and LL WBSF values and degraded 38-kDa desmin (DES; P < 0.01). Day-7 ST-steak WBSF value was greater than all other days ( P < 0.01) and day-14 steaks had greater WBSF value than remaining days ( P < 0.05). Day-28 ST-steak WBSF values were greater than day 56 and 112 ( P < 0.01), which did not differ ( P = 0.53). In the LL, day-7 steaks had greater WBSF values than the other two timepoints ( P < 0.01) and day-28 steaks had greater ( P < 0.01) WBSF values than day-112 steaks. Degraded ST 38-kDa DES content was less on day 7 and 14 compared to all other days ( P < 0.03), but did not differ ( P = 0.79) from each other. Days 28 and 56 38-kDa DES content was less than day 112 ( P < 0.01), but did not differ ( P = 0.34) from each other. Degraded LL 38-kDa DES content was less on day 7 than day 28 and 112 ( P < 0.02), which did not differ ( P = 0.67). There were LOC effects for only ST WBSF and muscle fiber CSA ( P < 0.05). Semitendinosus steak LOC 1 and 2 had greater WBSF values than all other locations ( P < 0.01), but did not differ ( P = 0.32) from each other. Semitendinosus steak LOC 3 and 5 had greater WBSF values than LOC 4 ( P < 0.01), but did not differ ( P = 0.85) from each other. The CSA of all ST fiber types were largest in LOC 1 compared to all other fiber types ( P < 0.01). The CSA of all LOC 2 and 3 fiber types was greater than LOC 4 and 5 ( P < 0.01), but were not different from each other ( P > 0.81), and LOC 4 had greater CSA than LOC 5 ( P < 0.01). Steak aging WBSF value improvements seemed proteolysis catalyzed, while the ST intramuscular tenderness gradient was more likely due to muscle fiber CSA.